Provokasi Sekitar Teologi Pembangunan Yang Kontekstual - Poli, WIM (Jurnal Jaffray, 2015)
Contextual Theology of Development speaks about possible efforts to overcome the unability of oneself and others to achieve a more meaningful life in oneâ€™s own surrounding, based on oneâ€™s faith. Whatever effort of development is undertaken, it is eschatological in nature. Wherever they are, Christians are called by Head of the Church to be partners of development within a civilized society, which is becoming more and more pluralistic in the era of globalization. Within such kind of society, the proper relationship with other partners of developmentÂ  is â€œI-Thouâ€ instead of â€œI-It.â€Â Teologi Pembangunan yang kontekstual berbicara tentang kemungkinan usaha membebaskan diri sendiri dan orang lain untuk mencapai tingkat kehidupan yang lebih bermakna, berdasarkan iman. Apa pun usaha pembangunan yang dilakukan, cirinya adalah eskatologis. Dimana pun orang Kristen berada, ia dipanggil ole Kepala Gereja untuk menjadi mitra pembangunan di dalam masyarakat yang beradab, yang kian menjadi majemuk di era globalisasi. Di dalam masyarakat sedemikian ini, hubungan antar mitra pembangunan yang tepat adalah â€œI-Thouâ€ ketimbang â€œI-It.â€Â